The aliphatic chain of cholesterol modulates bilayer interleaflet coupling and domain registration. Issue 19 (22nd September 2016) - Lin, Xubo; Zhang, Siya; Ding, Hui; Levental, Ilya; Gorfe, Alemayehu A.
Abstract : Cholesterol is a necessary component and critical regulator of liquid‐ordered membrane domains. However, the structural features that determine its unique physicochemical behaviors are not fully understood. In particular, very little is known about the specific functions of the terminal aliphatic chain of cholesterol, as previous studies have focused mainly on the rigid sterol ring structure and its hydroxyl head. In the current work, we used coarse‐grained molecular dynamics simulations to investigate the effect of cholesterol aliphatic chain length on the dynamics and structure of coexisting lipid domains. We found that the aliphatic chain has no appreciable effect on phase separation per se, but it significantly affects the rate of cholesterol flip‐flop and intermonolayer interaction. These effects are accompanied by changes in domain dynamics, lateral pressure, and interleaflet coupling. Our study provides useful insight into how biological sterols modulate communication between the outer and inner surfaces of the plasma membrane and, therefore, cellular signaling. Abstract :